2018
DOI: 10.2136/sssaj2017.12.0433
|View full text |Cite
|
Sign up to set email alerts
|

Soil‐Test Biological Activity with the Flush of CO2: I. C and N Characteristics of Soils in Corn Production

Abstract: Nitrogen limits crop production when insufficient and harms the environment when excessive. Tailoring N inputs to cropping systems remains a high priority to achieve production and environmental goals. We collected soils from 47 corn (Zea mays L.) production fields in North Carolina and Virginia at depths of 0 to 10, 10 to 20, and 20 to 30 cm and evaluated soil C and N characteristics in association with soil N mineralization. Soil organic C at a depth of 0 to 10 cm varied among sites from ~10 to 80 g kg -1 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 34 publications
7
49
2
Order By: Relevance
“…Culman et al (2013) reported a lack of management (tillage) system effect on Solvita CO 2 and suggested that treatment differences could have been masked by spatial heterogeneity in the field. The Solvita test has been used to predict crop N uptake and soil N availability (Franzluebbers, 2018; Franzluebbers et al, 2018), but there are concerns regarding cross‐laboratory reproducibility of results (Sullivan and Granatstein, 2015; Wade et al, 2018). Standardized protocols would improve the robustness of CO 2 flush tests, as demonstrated by variations in mineralizable C resulting from procedural differences including water delivery method (Franzluebbers and Haney, 2018; Wade et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Culman et al (2013) reported a lack of management (tillage) system effect on Solvita CO 2 and suggested that treatment differences could have been masked by spatial heterogeneity in the field. The Solvita test has been used to predict crop N uptake and soil N availability (Franzluebbers, 2018; Franzluebbers et al, 2018), but there are concerns regarding cross‐laboratory reproducibility of results (Sullivan and Granatstein, 2015; Wade et al, 2018). Standardized protocols would improve the robustness of CO 2 flush tests, as demonstrated by variations in mineralizable C resulting from procedural differences including water delivery method (Franzluebbers and Haney, 2018; Wade et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In North Carolina, Roper et al (2017) reported that biological tests did not adequately differentiate between long‐term management systems, though tillage did affect WEON and total Haney N on two out of three soils, and soil health test results were not correlated with crop yields. The relationship of CO 2 flush with crop N uptake has already been established (Haney et al, 2001); recent research indicates that CO 2 flush is also strongly associated with N availability in the field (Franzluebbers, 2016, Franzluebbers et al, 2018). Additional work is still necessary for Solvita and other Haney indicators to predict biologically available N across a broader range of soils and management systems.…”
mentioning
confidence: 99%
“…Soil physical, chemical, and biological properties were described more fully in Franzluebbers et al (2018). Briefly, laboratory methods included:…”
Section: Methodsmentioning
confidence: 99%
“…The five routine soil measurements included: pH in water and 0.01 CaCl 2 (soil/solution ratio of 1:2.5, w/w), Mehlich III extractable phosphorus (soil test P or STP), Mehlich III extractable K (STK), and bulk density. We used a 300‐d aerobic incubation as the benchmark for estimated net N mineralization, as long‐term incubations have been found to be the most accurate in predicting N‐supplying power of soils (Campbell, Ellert, & Jame, 1993; Franzluebbers, Pershing, Crozier, Osmond, & Schroeder‐Moreno, 2018; Stanford, Legg, & Smith, 1973). We hypothesized that this test would best predict N response type, but realize this length of an incubation is not feasible for a soil N test, so we wanted to look at which rapid N tests of plant‐available N (Table 1) would correlate with the 300‐d incubation test.…”
Section: Methodsmentioning
confidence: 99%